Answer:
B. The graph of g(x) is the graph of g(x) is the graph of f(x) horizontally stretched by a factor of 3.
Step-by-step explanation:
Horizontal shifting right by c units,
![(x,y)\rightarrow (x-c,y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28x-c%2Cy%29)
Horizontally stretched by factor c.
![(x,y)\rightarrow (\frac{x}{c},y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28%5Cfrac%7Bx%7D%7Bc%7D%2Cy%29)
Vertically stretched by factor c. ( where, 0< |c|<1 )
![(x,y)\rightarrow (x,cy)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28x%2Ccy%29)
Horizontally compressed by a factor of c. ( where, |b| > 1 )
![(x,y)\rightarrow (cx,y)](https://tex.z-dn.net/?f=%28x%2Cy%29%5Crightarrow%20%28cx%2Cy%29)
Here,
![f(x) = x^2](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E2)
When f(x) is shifted 1/3 unit right,
Then, the transformed function is,
![g(x) = (x-\frac{1}{3})^2](https://tex.z-dn.net/?f=g%28x%29%20%3D%20%28x-%5Cfrac%7B1%7D%7B3%7D%29%5E2)
When f(x) is stretched horizontally by the factor of 3,
Then, the transformed function is,
![g(x)=(\frac{1}{3}x)^2](https://tex.z-dn.net/?f=g%28x%29%3D%28%5Cfrac%7B1%7D%7B3%7Dx%29%5E2)
When, f(x) vertically stretched by a factor of 3,
Then, the transformed function is,
![g(x)=3(x)^2](https://tex.z-dn.net/?f=g%28x%29%3D3%28x%29%5E2)
When, f(x) is horizontally compressed by a factor of 3,
Then, the transformed function is,
![g(x)=(3x)^2](https://tex.z-dn.net/?f=g%28x%29%3D%283x%29%5E2)
Hence, option B is correct.